Actividades recreativas para el desarrollo psicomotor de los niños y niñas del nivel inicial 2, paralelo “B” de la unidad educativa José Antonio Eguiguren “La Salle” de la ciudad de Loja periodo septiembre 2013-julio 2014 - Romero Córdova, Vanessa Lissette (2015)
The present work of investigation deals with to know the importance the recreational activities for the psicomotor development the children and children 2 initial level parallel “B” the Unit Educative José Antonio Eguiguren “La Salle” and the form like surpassing this problem by means of the game. The recreational activities are made in the free time voluntarily of the participants, can take place of individual or collective form offering to immediate satisfaction, diversion, rest, entertainment, expression of adventure, facilitating the socialization, development of the personality of the individual. In the investigation process the methods were used analytical, synthetic, deductive, hermeneutical – dialectic, descriptive. He was diagnosed by means of instruments to the children in the Unit Educative José Antonio Eguiguren “La Salle” of level 2 parallel “B” to determine if deficiencies in the psicomotricidad, balance, movement exist, in the corporal scheme, and the lack of stimulation on the part of the parents, by means of a program of recreational activities through game is used like education for the children of the Unit Educative already mentioned, such who allowed me to observe, to investigate, to analyze and to collect information soon to be able to contrast with the reality and to settle down conclusions and recommendations. Once obtained the results I have reached the conclusion that a small part of my population has not stimulated of a positive way the children. Whereas most of the children they have had a good stimulation of each boy.